MODERN VIEWS ON THE SURGICAL TREATMENT OF PATIENTS WITH THE CONSEQUENCES OF BURNS OF THE FINGERS OF THE HAND IN CHILDREN (literary review) - Abdurakhmonov Farrukhbek Saidazimovich; Madazimov Madamin Muminovich (Scholar Express Journals, 2024)
Thermal lesions pose a serious medical and economic problem. In industrialized countries, 300-380 cases of burns of various localization per 100,000 people are registered daily. Almost every minute, somewhere in the world, a person becomes a victim of burns with all the ensuing medical and social consequences.
Keywords: surgical treatment; burn; brush